2002
DOI: 10.1111/1467-6494.05018
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Structure of Cloninger's Seven‐Factor Model of Temperament and Character in a Japanese Sample

Abstract: Theoretical assumptions regarding the genetic and environmental structure of personality proposed in Cloninger's seven-factor model of temperament and character were verified in a Japanese sample by using the twin method. The Temperament and Character Inventory (TCI) was administered to 296 twin pairs ranging in age from 14 to 28 years old. Among four temperament dimensions (novelty seeking [NS], harm avoidance [HA], reward dependence [RD], and persistence [PS]), HA and PS showed significant additive genetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Ando and colleagues [18], for example, found among 296 Japanese twin pairs that Harm Avoidance and Persistence showed significant additive genetic contributions and no shared environmental effect, supporting the original theoretical assumption. Nevertheless, in their study, Novelty Seeking and Reward Dependence could be explained by both genetic and shared environmental factors.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Ando and colleagues [18], for example, found among 296 Japanese twin pairs that Harm Avoidance and Persistence showed significant additive genetic contributions and no shared environmental effect, supporting the original theoretical assumption. Nevertheless, in their study, Novelty Seeking and Reward Dependence could be explained by both genetic and shared environmental factors.…”
Section: Introductionmentioning
confidence: 75%
“…In contrast to Cloninger's assumptions, all three character dimensions could be explained exclusively by additive genetic and unique environmental contributions – unique environment is what makes twins growing up in the same family dissimilar rather than similar, while the common environment is what makes twins similar. Moreover, the genetic components of Self-directedness and Cooperativeness were derived from those of the temperament dimensions [18]. The character traits have indeed shown much the same levels of heritability as the temperament traits across several studies [19], [20].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The seven main TCI dimensions comprise 25 facets. The TCI has generated a large and influential body of literature, spanning topics including the genetic heritability of personality (Ando et al, 2002), personality variability within Axis I diagnoses (e.g., Fassino et al, 2002), and the impact of personality on psychotherapy outcome (Joyce, Mulder, McKenzie, Luty, & Cloninger, 2004). …”
Section: Methodsmentioning
confidence: 99%
“…His ideas are of great importance, although some of them have not found empirical support. For example, twin studies have demonstrated that character traits such as self-directedness show high heritability estimates, comparable to heritability estimates of temperament traits [21, 22]. Moreover, genetic association studies have shown that diverse neurotransmitter systems (not limited to one system per temperament) are involved in the foundation of temperaments and character [23].…”
Section: Biologically Oriented Personality Psychologists - From Eymentioning
confidence: 99%